ANALISIS TENAGA KERJA MIGRAN PROVINSI NUSA TENGGARA BARAT - RIFKI KHOIRUDIN; EKA NURJANNAH; AGUS SALIM (LP2MTBM MAKARIOZ, 2023)
Purpose from research .ini be to find Determinants worker migrant Indonesian at Island Southeast West. Data that Used deep research .ini be data secondary from Body Navel Statistics (BPS) and Body Protection Power Work Indonesian (BP3MI). By dimension time research .ini use data Panel that be Combined data time-series and Cross-sectional to 10 province and city at NTB era 2019-2021. Method that Used deep research .ini be Regression data Panel. Result research .ini show that variable poverty and Index Building Human Influential Significant towards sum TKI. At side other GRDP, unemployment and average education not Influential Significant towards sum worker migrant. At side other all variable free Influential Significant towards sum TKI at Island Southeast West.